Association of diabetes mellitus and admission glucose levels with outcome after endovascular therapy in acute ischaemic stroke in anterior circulation. (1st July 2022) - Genceviciute, Kotryna; Göldlin, Martina B.; Kurmann, Christoph C.; Mujanovic, Adnan; Meinel, Thomas R.; Kaesmacher, Johannes; Seiffge, David J.; Jung, Simon; Mordasini, Pasquale; Fischer, Urs; Gralla, Jan; Sarikaya, Hakan; et al.
Abstract: Background and purpose: We aimed to assess the association of diabetes mellitus (DM) and admission hyperglycaemia (AH), respectively, and outcome in patients with acute ischaemic stroke with large vessel occlusion in the anterior circulation treated with endovascular therapy (EVT) in daily clinical practice. Methods: Consecutive EVT patients admitted to our stroke centre between February 2015 and April 2020 were included in this observational cohort study. Patients with versus without DM and with versus without AH (glucose ≥ 7.8 mmol/L) were compared. Results: We included 1020 patients (48.9% women, median age = 73.1 years); 282 (27.6%) had DM, and 226 (22.2%) had AH. Patients with versus without DM less often showed successful reperfusion (odds ratio [OR]adjusted  = 0.61, p  = 0.023) and worse 3‐month functional outcome (modified Rankin Scale [mRS] = 0–2: 31.3% vs. 48%, ORadjusted  = 0.59, p  = 0.004; death: 38.9% vs. 24.1%, ORadjusted  = 1.75, p  = 0.002; mRS shift: p adjusted  < 0.0001; if moderate/good collaterals and mismatch, mRS = 0–2: ORadjusted  = 0.52, p  = 0.005; death: ORadjusted  = 1.95, p  = 0.005). If analysis was additionally adjusted for AH, only mRS shift was still significantly worse in patients with DM ( p adjusted  = 0.012). Patients with versus without AH showed similar successful reperfusion rates and worse 3‐month functional outcome (mRS = 0–2: 28.3% vs. 50.4%, ORadjusted  = 0.52, p  < 0.0001; death: 40.4% vs. 22.4%, ORadjusted  = 1.80, p  = 0.001; mRS shift: p adjusted  < 0.0001; if moderate/good collaterals and mismatch, mRS = 0–2: ORadjusted  = 0.38, p  < 0.0001; death: ORadjusted  = 2.39, p  < 0.0001). If analysis was additionally adjusted for DM, 3‐month functional outcome remained significantly worse in patients with AH (mRS = 0–2: ORadjusted  = 0.58, p  = 0.004; death: ORadjusted  = 1.57, p  = 0.014; mRS shift: p adjusted  = 0.004). DM independently predicted recurrent/progressive in‐hospital ischaemic stroke (OR = 1.71, p  = 0.043) together with admission National Institutes of Health Stroke Scale score (OR = 0.95, p  = 0.005), and AH independently predicted in‐hospital symptomatic intracranial haemorrhage (OR = 2.21, p  = 0.001). The association of admission continuous glucose levels and most outcome variables was (inversely) J‐shaped. Conclusions: Hyperglycaemia more than DM was associated with worse 3‐month outcome in the patients studied, more likely so in the case of moderate/good collaterals and mismatch in admission imaging. Abstract : This study comprehensively elucidates the association of diabetes mellitus and admission hyperglycaemia and outcome after endovascular therapy at a tertiary care centre in an observational cohort of acute ischaemic stroke patients with large vessel occlusion in the anterior circulation treated in daily clinical practice. Admission hyperglycaemia more than diabetes mellitus was associated with worse 3‐month outcome in the patients studied, more likely so in the case of moderate/good collaterals and mismatch in admission imaging. Further studies should investigate a sufficiently large number of acute ischaemic stroke patients, reperfusion, faster treatment algorithms, treatment options without hypoglycaemia risk, glucose target levels for treatment initiation, and optimal frequency of measurements of glucose levels.